Military executions during WWII: The case of David Cobb - Lilly, J. Robert (American journal of criminal justice, 1995)
While few topics today generate more heated debate in American criminal justice than capital punishment, little attention has been directed to the one institution other than civilian courts that can execute U.S. citizens: the military. This article calls attention to this oversight and provides general descriptive information about military executions during WW II’s European Theater of Operations (ETO), and a more detailed examination of the ETO’s first execution. It illustrates several striking features of other ETO executions: predominately Black males with White victims, speedy trials, weak defense efforts and an appeal processes subject to illegal influence of commanders. In view of the U.S. Supreme Court’s 19% decision (9–0) in Loving v. United States upholding the constitutionality of the military executions and disproportion of minorities on Levenworth’s death row, the data reported here is timely and important for comparative research and the death penalty debate.